Beyond the bell: exploring the link between time allocation on extracurricular activities and academic performance in Chinese adolescents - Peng Zhang; Yifan Wang; Xuan Chen; Wei Yan; Yijie Zhu; Kaiping Peng (International Journal of Adolescence and Youth, 2023)
ABSTRACTAcademic performance could have an impact on job trajectories and socioeconomic status for societies in the future. However, only a few studies have focused on the impact of time allocation on extracurricular activity strategies. Based on that observation, we recruited 91,161 school students from 451 primary, middle, and high schools in China, and used a cross-sectional compositional data analysis approach to investigate the linkage between extracurricular activities and time allocation strategies and academic performance. Our study found that, in general, a suitable daily sleep routine is of primary importance in improving students’ academic performance. Additionally, daily exercise appears to be able to significantly facilitate higher academic performance. it’s important to note that exercising while sleep-restricted may have adverse effects. The most effective way to improve student academic performance proves to be reducing the time spent playing video games and watching short videos and replacing it with hours of sleep or exercise.